Design of an educational platform based on augmented reality for the special education of children with dyscalculia - Jhair Baltodano-Payahua; Sebastian Ramos-Cosi; Alicia Alva-Mantari; Gustavo Villar-Mayuntupa; Enrique Lee Huamani; Meyluz Paico-Campos; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2026)
Dyscalculia is a learning disorder that affects between 3% and 8% of the world's population and is characterized by difficulty in acquiring basic mathematical concepts, mainly in children. In view of this, several technological tools have been explored that can help improve the education of these children, with augmented reality (AR) being a promising alternative. The objective of this research is to design an AR-based platform to support the special education of children with dyscalculia. An agile methodology, Scrum, was used for the development, which allowed for an interactive approach to the design of the prototypes. Consequently, these were evaluated and validated by six experts in the field. The result was an acceptance rate of 81.2%, demonstrating the viability of the prototype. It is concluded that the prototype using AR is an effective tool to support children with dyscalculia aged 8 to 10, as it allows for an interactive and beneficial learning experience to nurture their knowledge.